Comparison of the In-Vitro Effects of Bevacizumab, Mitomycin-C, 5-Fluorouracil, and Triamcinolone Acetonide on the Viability of Cultured Human Tenon’s Fibroblasts - Pius Jonas Ocampo, MD; Ma. Margarita Lat-Luna, MD; Joseph Anthony Tumbocon, MD; Polly Chao-Po, MD; Andrei Martin, MD (Philippine Journal of Ophthalmology)
Objective: To evaluate and compare the effects of bevacizumab, mitomycin-C (MMC), 5-fluorouracil (5-FU), and triamcinolone acetonide (TA) on the viability of cultured human Tenon’s capsule fibroblasts (cHTF) in vitro.